Conducting Icos as a Modern Investment Approach for Implementation of Innovations for the Ukrainian Railway Transport - Zaitseva, I; Ieromina, M; Prudius, Y (International Journal of Engineering and Technology, 2018)
The Ukrainian railway transport is the leading branch in the national road transport complex. Until recently, the Ukrainian railways have been satisfying the transportation needs of the economy and the population. Today, the service life of the technical resource of railways is practically expired. Therefore, there is a threat that the railway transport fails to satisfy future transportation needs of the Ukrainian economy.According to the accounting reports of Ukrzaliznytsya PJSC, at the end of 2016, the deterioration level of the fixed assets in the industry was 69.4%. In the context of a constant budget shortfall, the most urgent issue for Ukrainian railways is focusing on activation of innovation activity. We believe that most of the schemes of the traditional economy in the 21st century no longer work; therefore, alternatives should be searched for, the most obvious of which now is the cryptoeconomy with its decentralized system. The development and implementation of innovations in the Ukrainian railway industry requires new approaches to the system of financing innovations in the country; in this respect, ICO is a modern and promising method of attracting investments.Â Â